PERAN NEGARA DAN PENERAPAN PANCASILA DALAM MEWUJUDKAN NEGARA KESEJAHTERAAN (WELFARE STATE) DI INDONESIA - Belinda Gunawan (Jurnal Paradigma Hukum Pembangunan, 2019)
The position of Pancasila as the basis of the state has given a consequence that the implementation of Indonesia as a rule of law-based state, including to create a welfare state condition, has to be based on Pancasila. The format of this research is a juridical-normative, it means the research used the secondary data. The typology of this research is prescriptive, that gave advice, solution and suggestion for this research. The purpose of this research is to find out the concept of welfare state in Indonesia, and to give usable advice to current state implementation. The result of this research is that welfare state concept in Indonesia is the welfare state which prioritize citizen's welfare, based on the principle of family system with the principle of togetherness, efficiency with justice, continuity, environmental perspective, self-sufficiency and keeping a balance in progress and unity of the national economy, as written in The Constitution of Republic Indonesia 1945. The ideal role of Indonesia to realize a welfare state is to concern on the role as the leader, law and policy maker, also a supervisor which drives the society (including private sector and individual) based on the values of Pancasila, especially the 5th principle (sila ke-5), to work together to increase the welfare in Indonesia, based on their own roles.